Sustainable city: perspectives and challenges. A systematic review between 2012 - 2022 (LACCEI, 2024)
The objective of this systematic review was to analyze the set of scientific articles of a theoretical and empirical nature on the sustainable city in the last 10 years. From the systematization of the databases, we obtained: Scopus 721 articles, Redalyc 882 articles, Dialnet 623 articles, Scielo 673 articles, ProQuest 886 articles and Ebsco 941 articles and 50 scientific articles were selected. The inclusion criteria were the last 10 years, scientific articles, language, variable and open access. It is concluded that it is relevant to evaluate the social, economic and environmental impacts, seeking to ensure that the present and future generations can meet their needs. On the other hand, there is no model to follow to achieve a sustainable city. A sustainable city is a city resilient to the adverse impacts of climate change that identifies and reduces the vulnerabilities of its population and increases adaptive capacity, as well as optimally manages disaster risks.